Investigation of one task of the potential theory - Domarkas, Aleksas; Rakauskas, Rimantas-Jonas; Vošterienė, Svajonė (Lietuvos matematikos rinkinys, 2002)
Using computer algebra package Maple we compute aproximative analytical solution. For Clebsch–Gordan coefficients was used sparse matrix array.